(untitled) (AYUSHDHARA, 2020)
Vatarakta, classified as a Mahavatavyadhi and as a separate disease in the scriptures has evoked attention of the Ayurvedic physicians and scholars because of its versatility in symptoms. Focussing on a single disease elaborated in modern science and equate it to Vatarakta cannot be considered as an apt methodology. Rather, Vatarakta can be understood as a conglomeration of different diseases such as autoimmune disorders, peripheral arterial disease and gouty arthritis to name a few. In this case study, a 42 year old male patient diagnosed with peripheral vascular disease was treated with the aid of the principles of Vataraktachikitsa and medications suitable to the disease under consideration. Shamana modality of treatment was advocated for the patient. The findings were obtained with timely monitoring of the symptoms and condition of the disease. Medications which included Shilajatu, Guggulu tiktakakashaya and Jatyaditaila provided significant relief.